Clinical Presentation of a Patient with Localized Acquired Cutis Laxa of Abdomen: A Case Report - Tugomir Gverić; Marko Barić; Vedrana Bulat; Mirna Šitum; Jana Pušić; Dubravko Huljev; Boris Zdilar; Snježana Gverić-Ahmetašević; Davor Tomas (Dermatology Research and Practice)
Background. Cutis laxa (CL) is a rare disorder of elastic tissue characterized by loose, sagging skin with reduced elasticity, and resilience without resulting scarring. CL may be inherited as a dominant, recessive, or X-linked recessive disease, or acquired. The heritable forms of CL predominantly begin at birth, but it may be delayed until puberty or age of 30 years with extracutaneous manifestations including pulmonary emphysema, umbilical and inguinal hernias, and gastrointestinal and vesicourinary tract diverticuli. An acquired form of the disease occurs in adults with no evidence of internal organ involvement. Objective. The aim of this case report was to present our patient suffering from CL, and to evaluate clinical presentation, diagnostic and therapeutic difficulties in this rare condition. Case Report. A 30-year-old female patient was admitted to our Hospital due to localized loose and sagging skin of abdomen, induced by prior cesarean section 6 years ago. CL has been diagnosed based on the clinical picture and pathohistological appearance. Conclusion. Reconstructive surgery provides a dramatic cosmetic improvement with significant psychosocial benefit. Repeated surgical procedures may be required to correct the lax skin, which worsens with age.